OP103 Enhancing Legitimacy And Coherent Value Appraisal Across Interventions In Healthcare And Social Services: Strategy Of The Québec Agency. (23rd December 2022) - Goetghebeur, Mireille; Wagner, Monika; Ganache, Isabelle; Demers-Payette, Olivier; De Guise, Michèle
Abstract : Introduction: The Institut national d'excellence en santé et en services sociaux (INESSS) makes recommendations regarding introduction, coverage, optimal use or withdrawal of interventions in physical and mental health and social services to support fair and reasonable decisions. The objectives of this work were to develop a statement of principles and ethical foundations for a common appraisal framework across diverse interventions, to enhance legitimacy and coherence of evaluation practices, and develop reflective approaches throughout the institution to operationalize the principles. Methods: To develop this statement, INESSS reviewed its practices across different units, surveyed the literature on innovative practices and the evolution of HTA, and undertook an extensive internal and external consultative process. The principles are used to develop reflective activities as part of a continuous improvement strategy. Results: The adopted approach to value appraisal considers the contributions of interventions to the Triple Aim of health and social services systems as well as their organizational and sociocultural feasibility and impacts (clinical, populational, economic, organizational, sociocultural dimensions). This approach is articulated around five principles including: (i) evaluating the most relevant objects and adapting evaluation modalities; (ii) mobilizing and integrating diverse types of knowledge; (iii) supporting multidimensional deliberation including diverse perspectives; (iv) developing fair and reasonable recommendations; (v) promoting value creation by supporting the implementation of recommendations and re-evaluation. Although all principles contribute to the legitimacy and credibility of the recommendations, which we aim to implement and consolidate through a set of activities, deliberation is an important part of the process that we are striving to improve. A first set of reflective activities are planned to support its operationalization, including: materials to promote a common understanding of the diverse aspects of the deliberation, reflective workshops on selected past projects, and sharing emerging reflections across INESSS units to further continuous improvement in operationalizing the principles. Conclusions: Moving forward, INESSS's strategic intention is to mobilize its staff and collaborators to facilitate the rigorous, agile and coherent application of these principles.